2022
DOI: 10.3390/ijerph191710611
|View full text |Cite
|
Sign up to set email alerts
|

A Multilevel Analysis of the Associated and Determining Factors of TB among Adults in South Africa: Results from National Income Dynamics Surveys 2008 to 2017

Abstract: TB is preventable and treatable but remains the leading cause of death in South Africa. The deaths due to TB have declined, but in 2017, around 322 000 new cases were reported in the country. The need to eradicate the disease through research is increasing. This study used population-based National Income Dynamics Survey data (Wave 1 to Wave 5) from 2008-to 2017. By determining the simultaneous multilevel and individual-level predictors of TB, this research examined the factors associated with TB-diagnosed ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 16 publications
(22 reference statements)
0
2
0
Order By: Relevance
“…Studies in India have shown undernutrition to be among the strongest determinants for TB risk [ 15 ]. In South Africa specifically, poor living conditions, unemployment, low SES, age and male gender, race, smoking, and marital status have all been identified as contributing to TB risk [ 16 21 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies in India have shown undernutrition to be among the strongest determinants for TB risk [ 15 ]. In South Africa specifically, poor living conditions, unemployment, low SES, age and male gender, race, smoking, and marital status have all been identified as contributing to TB risk [ 16 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Compared to medium or high-TB-incidence countries, the effect sizes for alcohol abuse, homelessness, and intravenous drug use are stronger in low-incidence populations [ 22 ]. In South Africa, multilevel modeling approaches have shown that provincial [ 16 ] and community income inequality [ 18 ] have strong effects on TB incidence and progression, independent of individual-level risk factors.…”
Section: Introductionmentioning
confidence: 99%